The Analysis of Stress Management to Improvement Employess Performance Case Study at The Service Section of PT Pos Indonesia (Persero) Bandung 40000 - Rozano, Randy; Febriansyah, Hary (The Indonesian Journal of Business Administration, 2016)
Abstract - As a company engaged in the service, PT. Pos Indonesia is obliged to give the best service to customers. Changes in the condition of the organizational structure and the rapid advancement of the times, demanding human resources to participate to provide the best performance for the company. So also occurred in PT. Pos Indonesia, especially in the service is the frontline companies, so often these problems will cause stress on employees. The employees at the service section should always be able to be kind and friendly in any condition, which eventually led to the stress that occurs on the employee. This research uses two methods: quantitative and qualitative and carried out to see if there is happen the eustress (positive stress) or distress (negative stress) at the service of the PT. Pos Indonesia (Persero) Bandung 40000. There are two factors causing stress, that stress individual and organizational stress. Stress individuals represented by four variables: role conflict, workload, career development, and relationships at work. Stress organizations represented by two variables, namely the organizational structure and leadership. Both of these factors will be linked to the performance of employees, so it can be known whether stress raise or lower the performance on the employee's performance. This study uses census, where all the employees in this part of the informant research. All data that can be processed using multiple linear regression method for known patterns of stress that occurs, the correlation of the performance and its effect on performance. In addition qualitative methods such as interviews conducted to strengthen the research results. The results obtained from this study was the occurrence of eustress in two variables on individual stress factors, namely: career development and relationship at work, as well as a variable in organizational stress factors, ie leadership. While distress occurs in two individual stress variables, ie conflict of roles and workloads, as well as a variable in the stress of the organization, namely the organizational structure. The results are expected to help and become inputs for the company to improve the state of employee stress causing a decline in the performance of the employee caused by the patterns of distress.Â Keywords: Job stress, Individual stress, Organizational Stress, Performance, Multiple Linear Regression